[PROVISIONAL] Genetic evidence for a species complex within the piranha Serrasalmus maculatus (Characiformes, Serrasalmidae) from three Neotropical River basins based on mitochondrial DNA sequences - Thaís Souto Bignotto; Thiago Cintra Maniglia; Vivian Nunes Gomes; Isadora Janolio de Oliveira; Carlos Sérgio Agostinho; Sônia Maria Alves Pinto Prioli; Alberto José Prioli (Genetics and Molecular Biology)
Abstract Mitochondrial molecular markers (DNA sequences of D-loop, cytochrome b and cytochrome c oxidase I) were employed to characterize populations of the piranha Serrasalmus maculatus from Upper Paraná, Upper Paraguay and Tocantins River basins. D-loop sequences of S. maculatus population from Paraná-Paraguay River basin exhibited tandem repeats of short motifs (12 base pairs) and variable numbers, depending on specimens, accounting for length variation. Concatenated mitochondrial sequences suggested that S. maculatus encompass different mitochondrial DNA lineages. Although sampling was restricted to three river basins, phylogenetic analysis clearly indicated that the species currently recognized as S. maculatus presents high genetic variability. Maximum likelihood and Bayesian analysis clustered S. maculatus populations according to their locations. However, the highest genetic differentiation was identified between populations from Paraná-Paraguay system and Tocantins River basin. Three species delimitation analyses (PTP, GMYC and ABGD) suggested that are at least two species among the analyzed populations. The analysis of the mitochondrial sequences evidenced genetic differentiation among populations corresponding to related, but different species, suggesting that, at least, S. maculatus from Tocantins River and Paraná-Paraguay River basins are most likely different species. Therefore, S. maculatus should be considered a complex of species with morphologically cryptic diversity. An integrative revision is suggested. text